Extended treatment with edoxaban in cancer patients with venous thromboembolism: A post‐hoc analysis of the Hokusai‐VTE Cancer study. (25th July 2019) - Di Nisio, Marcello; van Es, Nick; Carrier, Marc; Wang, Tzu‐Fei; Garcia, David; Segers, Annelise; Weitz, Jeffrey; Buller, Harry; Raskob, Gary
Abstract: Background: Patients with active cancer and venous thromboembolism (VTE) are at high risk of recurrence. Therefore, continued anticoagulant therapy beyond the initial 6 months is suggested in this patient population, but evidence supporting this approach is limited. Methods: The Hokusai VTE Cancer trial compared edoxaban with dalteparin for VTE treatment in patients with active cancer. This post hoc analysis focused on the follow‐up period from 6 to 12 months. The primary outcome was the composite of adjudicated first recurrent VTE or major bleeding. Secondary outcomes included recurrent VTE, major bleeding, and clinically relevant bleeding. Results: Of the 522 and 524 patients randomized to edoxaban or dalteparin, 294 (56%) received edoxaban and 273 (52%) received dalteparin for more than 6 months (median duration of 318 and 211 days, respectively). Between 6 and 12 months, the primary outcome during study treatment occurred in seven patients (2.4%) in the edoxaban group and six patients (2.2%) in the dalteparin group (unadjusted hazard ratio 1.05; 95% confidence interval, 0.36‐3.05). Recurrent VTE occurred in two patients (0.7%) in the edoxaban group and in three patients (1.1%) in the dalteparin group, whereas major bleeding occurred in 5 (1.7%) and three patients (1.1%), respectively. Conclusions: The rates of recurrent VTE or major bleeding are relatively low among patients with active cancer receiving extended anticoagulant therapy beyond 6 months. Extended treatment with oral edoxaban appears as effective and safe as subcutaneous dalteparin.